2019
DOI: 10.1111/jpy.12850
|View full text |Cite
|
Sign up to set email alerts
|

The systematics of Lobophora (Dictyotales, Phaeophyceae) in the western Atlantic and eastern Pacific oceans: eight new species

Abstract: Lobophora is a common tropical to temperate genus of brown algae found in a plethora of habitats including shallow and deep‐water coral reefs, rocky shores, mangroves, seagrass beds, and rhodoliths beds. Recent molecular studies have revealed that Lobophora species diversity has been severely underestimated. Current estimates of the species numbers range from 100 to 140 species with a suggested center of diversity in the Central Indo‐Pacific. This study used three molecular markers (cox3, rbcL, psbA), differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 55 publications
(142 reference statements)
5
49
0
Order By: Relevance
“…(, )and Camacho et al. () subsequently confirmed that the diversity in the Greater Caribbean was much higher than previously assumed (Table , Fig. ) with the report of nine (Schultz et al.…”
Section: List Of the 15 Lobophora Species From The Greater Caribbean supporting
confidence: 52%
See 4 more Smart Citations
“…(, )and Camacho et al. () subsequently confirmed that the diversity in the Greater Caribbean was much higher than previously assumed (Table , Fig. ) with the report of nine (Schultz et al.…”
Section: List Of the 15 Lobophora Species From The Greater Caribbean supporting
confidence: 52%
“…() and Camacho et al. () demonstrated that different morpho‐ or eco‐types represent different species. Sun et al.…”
Section: List Of the 15 Lobophora Species From The Greater Caribbean mentioning
confidence: 99%
See 3 more Smart Citations